The influence of semi-fowler sleeping position education on sleep quality in congestive heart failure patients at Subang General Hospital - Ariyani, Wina; Luthpiah, Nazla (Indonesian Nursing Journal, 2024)
Background: Patients with congestive heart failure (CHF) frequently experience nocturnal dyspnea, leading to poor sleep quality, which can slow down recovery and prolong hospital stays. The semi-Fowler sleep position may alleviate breathing difficulties and improve sleep quality in CHF patients. Purpose: This study aimed to evaluate the impact of semi-Fowler sleep position education on the sleep quality of CHF patients. Methods: A quasi-experimental design with a pre-test and post-test control group was used, involving 26 CHF patients selected through accidental sampling from the inpatient ward of Subang General Hospital. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), and the intervention involved educational booklets and demonstrations on the semi-Fowler sleep position. Results: Data analysis using the Mann-Whitney test showed a significant improvement in sleep quality post-intervention, with a p-value of 0.000, indicating a meaningful difference in sleep quality between the intervention and control groups. Conclusion: Educating CHF patients on the semi-Fowler sleep position significantly improved their sleep quality. These findings suggest that incorporating semi-Fowler position education into patient care may help reduce nocturnal discomfort and promote better recovery in CHF patients. This approach could be a practical intervention for improving patient outcomes and reducing hospital stays.